The Perspective of Students Toward Class Culture Between Students of Paramedical and Health Faculty in Golestan University of Medical Sciences - Leyla Jouybari; Nevisa Sadat Seyyedghasemi; Ahmad Taghavi; Fariba Baiky (Babol University of Medical Sciences, 2016)
BACKGROUND AND OBJECTIVE: One of the indicators of developed countries is the role of higher education system in the culture and civilization. It is important to Understand students;#39 initiatives and feelings to culture and relations of class members to planning, create positive changes, Organization and transformation. The perceptions of students from the class culture and their feeling about behaviors of teachers and classmates, can also lead to compatible or incompatible behaviors. The purpose of this study was to investigate the classroom atmosphere from attitudes of students in paramedical and health faculty in 2015. METHODS: This descriptive research by sectional method was done between 240 students of   paramedical and health schools. Data through two the standardized questionnaires demographic and Stephen Robbins class culture that have 8 questions with Likert 5 worth scale (from Totally agree untill totally disagree) was collected and Using SPSS version 16 and chi-square tests and Pearson correlations were examined. FINDINGS: The results showed that female's %73.3 of Sample population and males %26.2 have formed. 53% students were Residential and 47% non-residential. Average class culture among student was 27.45±4.986. Open class culture (more than 30) of% 35, borderline (20-29) %55 and close (less than 20) was 10% among students. Analytical results showed that there was a significant relationship between class culture with field (p=0.000), residence (residential and non residental) (p=0.059) and adjusted (p=0.023) but there was no significant relationship between age (p=0.791), sex (p=0.299), indigenous and non-indigenous (p=0.452) and marital status (p=0.604)). CONCLUSION: In the viewpoints of most medical students, class culture was borderline And articulate masters of expectations, more interaction and relashionship with students and using student - centered methods can lead to more relationship between teachers and students and the students themselves, and create a culture of open and friendly, and it is presented as a way to increase class culture that is an important factor in academic performance .